A discursive psychology study of epistemic primacy in an LGBTQ+ youth group's textual educational materials. (March 2020) - Uttamchandani, Suraj; Lester, Jessica Nina
Highlights: We use discursive psychology to analyze how LGBTQ+ youth build up their authority. We study slide decks created by an LGBTQ+ youth group for presentations they gave to teachers and others. We found that four discursive strategies were used to manage youth's epistemic rights. Abstract: In this paper, we contribute to scholarship around how epistemic rights are managed discursively by considering how LGBTQ+ youth construct their arguments. We take up a critical perspective to understand how these discursive practices function in a language climate where LGBTQ+ youth's epistemic primacy over issues affecting them is potentially delegitimized through ageism, heterosexism, and genderism. Specifically, we draw upon discursive psychology to analyze how LGBTQ+ youth build up their epistemic primacy and minimize audience critique. Drawing from a larger ethnographic study, we analyzed textual data in slide decks (i.e., PowerPoint slides) created by an LGBTQ+ youth group for presentations they gave to teachers and other youth-serving professionals about working with LGBTQ+ youth. We found that four discursive strategies were used in the slide decks to manage the youth's epistemic rights, including: (1) using factual claims and outside corroboration, (2) claiming experiential expertise, (3) refuting anticipated critique, and (4) articulating limitations. This study's findings point broadly to how epistemic rights are built in textual data and specifically how minoritized youth construct text to be taken seriously.